2010
DOI: 10.1016/j.jhep.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased degranulation of natural killer cells during acute HCV correlates with the magnitude of virus-specific T cell responses

Abstract: Background/Aims-Natural killer (NK) cells provide early defense against viral infections by killing infected cells and producing cytokines that inhibit viral replication. NK cells also interact with dendritic cells (DCs) and this reciprocal interaction regulates both innate and adaptive immunity. Genetic studies have suggested that NK cell activity is a determinant of HCV infectious outcome but a functional correlation was not established. We hypothesized that increased NK cell activity during acute HCV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 48 publications
10
92
1
2
Order By: Relevance
“…3 The exact role of NK cells in HCV infection, however, remains elusive, because current studies have yielded inconsistent results regarding phenotype and function of NK cells. [4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The exact role of NK cells in HCV infection, however, remains elusive, because current studies have yielded inconsistent results regarding phenotype and function of NK cells. [4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, published data on phenotype and function of NK cells in HCV infection are controversial. [4][5][6][7][8][9][10][11][12][13] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Elletier et al, (2010) In line with this, a Japanese study demonstrated that combination therapy of pegylated interferon (IFN-α) and ribavirin improved NK distribution and functions, and significantly increased their numbers among HCV -cleared patients. The authors observed that relapsing patients failed to recover NK functions and numbers, these results suggest that NK alteration caused by HCV infection may be due to the impairment of cellular immune response, which might result in chronic diseases.…”
Section: Resultsmentioning
confidence: 77%
“…Werner et al describe a strong NK cell response in healthcare workers with low-level HCV exposure but do not develop into acute HCV infection [30]. Notably, Pelletier et al find an increased NK cell degranulation in early phase of HCV infection in a cohort of intravenous (IV) drug users who cleared HCV spontaneously [31]. Peter et al [32] also suggest that sustained NK cell activation protected highly-exposed uninfected injecting drug users from HCV infection.…”
Section: Nk Cells and Hcv Infectionmentioning
confidence: 99%